Guide to solutions for inorganic chemistry - Strauss, S H (Oxford Univ. Press, 1999)
This book covers all of the self-test and exercises in the textbook Inorganic Chemistry, 3rd edition,... A special feature o Guide to solutions is a Quiz at the end of each chapter consisting of ten questions.